Determining post-operative morbidity and mortality following gynecological oncology surgery: protocol for a multicenter, international, prospective cohort study (Global Gynaecological Oncology Surgical Outcomes Collaborative—GO SOAR). Issue 9 (September 2021) - Gaba, Faiza; Bizzarri, Nicolò; Kamfwa, Paul; Saiz, Allison; Blyuss, Oleg; Paranjothy, Shantini; Ramirez, Pedro T; Cibula, David; Elshami, Mohamedraed; Saad, Mahmoud; Nafea, Ahmed; Elhadi, Muhammed; et al.
Abstract : Background: The Global Gynaecological Oncology Surgical Outcomes Collaborative (GO SOAR) aims to develop a network of gynecological oncology surgeons, surgical departments, and other interested parties that will have the long-term ability to collaborate on outcome studies. The protocol for the first collaborative study is presented here. Primary Objective: To evaluate international variation in 30-day post-operative morbidity and mortality following gynecological oncology surgery between very high/high and medium/low human development index country settings. Hypothesis: There is no variation in post-operative morbidity and mortality following gynecological oncology surgery between very high/high and medium/low human development index country settings. Study Design: International, multicenter, prospective cohort study. Patient data will be collected over a consecutive 30-day period through gynecological oncology multidisciplinary teams/tumor boards and clinics across different human development index country groups. All data are collected on a customized, secure, password protected, central REDCap database. Major Inclusion/Exclusion Criteria: Inclusion criteria include women aged ≥18 years undergoing elective/emergency, curative/palliative surgery for primary/recurrent tubo-ovarian/peritoneal, endometrial, cervical, vulval, vaginal, gestational trophoblastic malignancies. Surgical modality may be open, minimal access (laparoscopic/robotic), or vaginal. Primary Endpoint: 30-day post-operative morbidity and mortality defined as per Clavien-Dindo classification system. Sample Size: 1100 (550/arm). Estimated Dates for Completing Accrual and Presenting Results: It is estimated recruitment will be completed by 2022 and results published by 2023. Trial Registration: ClinicalTrials.gov registry: NCT04579861 (https://clinicaltrials.gov/ct2/show/NCT04579861 ).